2021
DOI: 10.4103/aja.aja_4_21
|View full text |Cite
|
Sign up to set email alerts
|

Testicular germ cell tumors type 2 have high RNA expression of LDHB, the gene for lactate dehydrogenase subunit B

Abstract: This study analyzed RNA expression of genes for three serum tumor markers, alpha fetoprotein (AFP), human chorionic gonadotropin (hCG), and lactate dehydrogenase (LDH), in patients with testicular germ cell tumors (TGCT) type 2. The gene AFP encodes AFP, the gene for chorionic gonadotropin beta polypeptide 5 ( CGB5 ) encodes a major part of the specific beta subunit of hCG, and the genes for LDH subunit A ( LDHA ), LDH subunit B ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Third, postoperative serum LDH is also a key factor for lung metastasis of tumors. Men with TGCTs have increased LDH levels in 40–60% of cases [ 21 , 22 ]. The level of serum LDH correlates with tumor burden and growth rate, as well as with cellular proliferation, and is typically higher in patients with advanced disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, postoperative serum LDH is also a key factor for lung metastasis of tumors. Men with TGCTs have increased LDH levels in 40–60% of cases [ 21 , 22 ]. The level of serum LDH correlates with tumor burden and growth rate, as well as with cellular proliferation, and is typically higher in patients with advanced disease [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…All three LDH isoenzymes can be encoded by LDHA, LDHB, and LDHC. Eyben et al [ 22 ] suggested that seminoma and non-seminomatous germ cell tumors have high RNA expression of LDHB. There are major biologic effects of LDHB.…”
Section: Discussionmentioning
confidence: 99%
“…LDH in animals is a tetramer, which is composed of two kinds of subunits, A and B, which can be assembled into four combinations. LDH exhibits five isozyme forms [ 42 ]. Among them, LDHB is mainly present in the myocardium, which catalyzes lactate and generates pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other malignancies, patients with TGCT have a unique isoenzyme pattern for serum lactate dehydrogenase (S-LDH) with an unusually high LDH isoenzyme 1 activity (S-LDH-1) [ 21 , 22 , 23 ]. LDH-1 is a tetramer of four LDHB subunits, generated from LDHB on the short arm of chromosome 12, 12p [ 24 ]. Of all malignancies, the international tumor, nodes, and metastases (TNM) classification incorporates serum tumor markers only for TGCT [ 25 ].…”
Section: Testicular Germ Cell Tumors Type IImentioning
confidence: 99%